Great Indian Economists vol.9 Their creative vision for socio-economic development -P.R. Brahmananda - Das, Debendra Kumar (ed) (New Delhi Deep & Deep Publications, 2004)
Professor P.R. Brahmananda : academic profiles and motivations to economics